Compliance status of tobacco control laws in the university setting of Bangladesh: an analytical study followed a mixed-method approach - Nasrin Akter; Bilkis Banu; Sujana Haque Chowdhury; Tahsin Tasneem Tabassum; Sarder Mahmud Hossain (BMJ Public Health)
Background Implementation of National Tobacco Control Laws (NTCLs) in university settings was found to be worse in Bangladesh.Objectives This study aimed to depict the compliance status of tobacco control laws (TCLs) and the associated factors following the university setting approach in Bangladesh.Methods This cross-sectional study was conducted with a mixed-method approach among the 385 students (quantitative method), 10 teachers and 10 administrative staff (qualitative method) of Northern University Bangladesh. Data were collected through mobile phone calling (quantitative) and in-depth interviews method (qualitative). Appropriate ethical issues were addressed. Logistic regression analysis was performed to find out the determinants. The study revealed non-satisfactory compliance with TCLs among 56.4% of study subjects which was strongly supported by the outcome of the qualitative approach. Predominant non-satisfactory compliance was found through the explorations of the conditions of buying and selling tobacco (78.4%), pasting no-smoking signage (3.2%), antitobacco advertisement within the university (34.8%) and specific university policy to implement NTCL. Non-satisfactory compliance was found significant among the younger aged (≤21 years: COR/p=2.74/0.01; 95% CI 1.27 to 5.92) from the first-year group (adjusted odds ratio (AOR)/p=2.28/0.02; 95% CI 1.15 to 4.49) who had moderate nicotine dependency (AOR/p=4.04/0.01; 95% CI 1.28 to 12.74), poor knowledge on TCLs (AOR/p=3.57/0.02; 95% CI 1.28 to 9.95) and the respondents who suggested family guidance (AOR/p=1.77/0.06; 95% CI 0.97 to 3.22) might be a sustainable way to minimise tobacco consumption in the university setting.Conclusions The study revealed some crucial factors for the non-satisfactory compliance status towards TCLs in the university setting. This empirical outcome and evaluation strategy can guide to plan of future large-scale studies, which may lead to implementing effective intervention programmes focusing on the development of a tobacco-free environment in the university setting.